Development of Integrated Tourism Destinations Based on Contextual Marketing vis-à-vis Digital Marketing - Akib, Haedar; ., Ismail; Suhardi Rahman, Edi; Basra, Jumase; Wahidiyat Haedar, Ahmad (KnE Social Sciences, 2024)
The tourism sector has experienced expansion, diversification, and intensification of sustainable management as one of the largest and fastest growing economic sectors in the world because it is developed in an integrated manner based on contextual or conventional marketing and virtual marketing, called digital marketing at once. This research article analyzes and explains the importance of contextual marketing as the basis of the value creation process for the development of integrated tourism destinations. The data, information, and knowledge regarding the focus on the research locus in the Province of South Sulawesi Indonesia were obtained through observations of several leading tourism destinations along with the author’s experience of visiting tourist destinations in the country and abroad as benchmarking. In addition, interviews and focus group discussions were conducted with stakeholders on tourism destinations. Qualitative descriptive analysis was carried out following an interactive model which included data collection, data condensation, data presentation, and verification or concluding. The results of the study found that the development of integrated tourism destinations based on contextual marketing strategies is related to generic marketing functions that are applied to strengthen tourism functions as a leading sector of sustainable multi-dimensional development. The development is carried out contextually or conventionally and virtually or referred to as tourism marketing in the air while still revitalizing the content, context, and infrastructure of tourism marketing. The success of integrated tourism development in the eyes of the public can be seen from the existence of social learning and knowledge creation processes that form a harmonious partnership-collaborative relationship in a Hexa-helix pattern. The basic values and value orientation of integrated tourism destination development both contextually and virtually or digitally marketing can be achieved when togetherness has become a necessity that is practiced. The effectiveness of its implementation is carried out - at least - through the 7-C’s public relations communication (PRC) approach which consists of credibility, context, content, clarity, continuity and consistency, channels, and capability of the audience as the basis of digital marketing. Keywords: tourism destinations, marketing mix, contextual marketing, digital marketing, hexa-helix